Comprehensive ro–vibrational analysis of di–deuterated hydrogen sulfide in the region of the ν2, 2ν2 and 2ν2−ν2 bands: The D232S, D234S, and D233S isotopologues. (September 2020) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Ersin, T.; Sydow, C.; Maul, C.; Bauerecker, S.
Abstract : highlights: FTIR spectra of the v2, 2v2, and 2v2- v2 bands of D2 32S, D2 34S, and D2 33S are recorded. Ground state parameters and pure rotational energies of D2 34S and D2 33S are determined. Band centers, rotational, centrifugal distortion and resonance interaction parameters of the (010) and (020) vibrational states are determined for all three iso topologues. Abstract: High–resolution infrared spectra of the D2 S molecule were experimentally recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer and theoretically analyzed in the region of 700 – 1800 cm − 1, where the ν 2 and 2 ν 2 bands are located. For the first time, transitions were assigned to the 2 ν 2 and 2 ν 2 − ν 2 bands of the D2 32 S and D2 34 S isotopologues. For the ground vibrational state and the ν 2 band of D2 34 S, the spectral information was considerably extended in comparison with preceding works. For the first time, transitions belonging to the rare D2 33 S hydrogen sulfide species were assigned to the ν 2 and 2 ν 2 bands, as well as a rotational structure of the ground vibrational state of D2 33 S was determined on the basis of experimental values of the ground state combination differences (maximum values of quantum numbers for used ground state combination differences were J max = 19, K a max = 8, Δ J max = 2, Δ K a max = 2 ). Sets of spectroscopic parameters of the Watson hamiltonian in A − reduction and I r − representation was determined for the (010) and (020) vibrational states of all three discussed species and for the ground vibrational states of D2 34 S and D2 33 S from the weighted fit of parameters of this hamiltonian. The d rms of reproduction of the initial experimental data for all nine vibrational states (three vibrational states for any species) is not far from 1 × 10 − 4 cm − 1 which is close to experimental errors in line positions.